Sustainable Construction Supply Chain Management in India, An Industry Perspective - Mudigonda, Aditya; Naik, M.Gopal; Dhilip, T. (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The built environment has a significant impact on both global and local environmental change. Every stage of the construction process has a substantial environmental impact. With growing environmental concerns, the construction sector is embracing a "go green" initiative. The proper execution of Supply Chain Management (SCM) in the industrial business has resulted in significant success. With the recent focus on environmental preservation and sustainability, as well as government pushes toward sustainable growth, firms are ready to use a green future strategy to increase market share and outperform competitors. The current study aims to provide an insight into the perspectives of various agents of construction supply chain and enhance the construction market sustainability. Further, the factors that influence supplier selection and sustainability are explored and the relevant supply chain participants' perspectives to the current state of sustainability in construction supply chains is investigated. In the current research the key trends in sustainable construction supply chain management are analysed using a sample of 279 responses from construction raw material manufacturers and suppliers, logistic teams, and end users. This study also will seek to determine how companies are understanding sustainable supply chain management processes and how it stands in their business in terms of cost, supply chain orientation and effectiveness. Relative Importance Index method (RII) is used to evaluate the responses of the survey. It was observed that the suppliers believe that they are doing enough to conserve resources and conserve the environment, while the clients perceive that the suppliers’ efforts are insufficient. While the manufacturing industries claim that emissions are measured on a regular basis, but only a few of them publish emission reports on their websites. Although the industry believes that adopting sustainable practices in manufacturing and along the supply chain will result in future cost savings and increased market penetration in dynamic markets, it has been observed that the initial high investments and a lack of proven models are impeding the adoption of sustainable practices. This research was limited to a small group of lime mining teams, raw material suppliers, logistics team members and end users of construction sector from Southern part of India. This study provides an understanding of the perspectives of the different construction supply chain participants regarding the various aspects of environmental, social and economic sustainability.